Corpos diferenciados e o processo de criação da performance Kahlo em Mim Eu E(m) Kahlo - Oliveira, Felipe Henrique Monteiro (2013)
The dissertation intends to develop an investigation on the artistic existence in human beings with different bodies in society at different historical moments. In this regard and based on this scenario, the study develops a description of the stigmas production and how they are established, spread and interfere with the sociability among human beings regarded as normal and those with different bodies. Regarding the scenic arts, the text describes about the participation of artists with different bodies in the scene, specifically the freak show and postdramatic theater. The text also investigates aspects of the biography and the work of mexican artist Frida Kahlo, which underpin methodological proceedings and produce contribution to the creative process of performance Kahlo em mim Eu e(m) Kahlo , which is to investigate the practice of the scene in this dissertation